Yaska Hawshi, the first Kurdish female poet (based on documents and field information) - Mohammed, Iraj Hussein (Sulaimani Journal for Humanities, 2026)
The history of Kurdish literature has not yet been written and reorganized. However, the position of our people's scholars and poets according to the ranking of their time, works and subjects has not yet been determined. Searching the contents and margins of documents and manuscripts reveals new information about other historical and literary figures. In the palace of Sheikh Abdul Mumin Mardokhi (written in 1198 AH) there is a poem by Yusuf and his mother Yaska. The poet Yaskay belonged to the Hawshi Jaff tribe. Based on source information about Yusuf Yaska (d. 1040 AH) and his life with Khan Ahmad Khan, Emir of Ardalan and the poet Besarani, as well as historical monuments about Yusuf Yaska and the Hawsh tribe (Hawari Hawshi, Hawsh village, etc.). We'll dig it up. Accordingly, more than two hundred years before Ms. Mastura Ardalan, the fingerprint of Kurdish poetry is visible in the pen of a female poet and Yaska Hawshi is identified as the first female poet in Kurdish poetry.
Keywords: Ardalan; Yusuf Yaska; Safavid; Zeran; Kalash; Zalm; Kosalan